High levels of type II Fusarium head blight resistance conferred in wheat by combining wheat gene Fhb1 with Lophopyrum elongatum gene Fhb7The2 - Jan Dvorak; Karin R. Deal; Patrick E. McGuire; Emily J. Conley; James A. Anderson; George Fedak; Julia A. Malvick; Han Chen; Hans-Georg Müller (Czech Journal of Genetics and Plant Breeding)
Wheat Fusarium head blight (FHB) leads to losses of grain yield and quality. Ingestion of diseased grain is detrimental to human health due to the mycotoxins present in the grain. Developing resistant cultivars for environments where FHB is prevalent is therefore an important breeding objective. One of the most effective wheat genes conferring type II resistance to FHB is Fhb1, originally discovered in the Chinese cultivar (cv) Sumai 3. Another excellent FHB resistance gene is Fhb7 located on the long arm of Lophopyrum elongatum chromosome 7E. Several alleles of Fhb7 have been identified. Allele Fhb7The2 was found in disomic substitution lines 7E(7A), 7E(7B) and 7E(7D) derived from amphiploid AgCS. The amphiploid was produced from a hybrid Triticum aestivum cv Chinese Spring × L. elongatum. To find if combining Fhb7The2 with Fhb1 confers higher resistance in wheat than single genes, an introgression line derived from AgCS and possessing Fhb7The2 was recurrently backcrossed to bread wheat cv Rollag and MN-Washburn possessing Fhb1. Experimental lines possessing both Fhb7The2 and Fhb1 were developed and validated cytogenetically and with the L. elongatum genome-wide Sequenom SNP MassARRAY. Spikes of these lines, parental cv Rollag and MN-Washburn, and those of disomic addition line 7E possessing Fhb7The2 plus controls were inoculated with Fusarium in a twice-replicated trial in controlled greenhouse environmental conditions. FHB infection rates were significantly lower in lines combining Fhb7The2 with Fhb1 than in materials with Fhb7The2 or Fhb1 alone.